(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article presents a scientific analysis of the theory and practice of carrying out significant work on the radical improvement and modernization of the management system at the present stage of the country’s development. The activity of the public administration system has contributed to the development of the experience of barchaprogressive speeches that have taken place in recent years.